Beneficial Effects of Evogliptin, a Novel Dipeptidyl Peptidase 4 Inhibitor, on Adiposity with Increased Ppargc1a in White Adipose Tissue in Obese Mice - Chae, Yu-Na; Kim, Tae-Hyoung; Kim, Mi-Kyung; Shin, Chang-Yell; Jung, Il-Hoon; Sohn, Yong Sung; Son, Moon-Ho (PLOS ONE, 2015)
Although dipeptidyl peptidase 4 (DPP4) is an adipokine known to positively correlate with adiposity, the effects of pharmacological DPP4 inhibition on body composition have not been fully understood. This study was aimed to assess the effects of DPP4 inhibitors on adiposity for the first time in the established obese mice model. The weight loss effects of multiple DPP4 inhibitors were compared after a 4 week treatment in diet-induced obese mice. In addition, a 2 week study was performed to explore and compare the acute effects of evogliptin, a novel DPP4 inhibitor, and exenatide, a glucagon-like peptide-1 (GLP-1) analogue, on whole body composition, energy consumption, various plasma adipokines and gene expression in white adipose tissue (WAT). After the 4 week treatment, weight loss and blood glucose reductions were consistently observed with multiple DPP4 inhibitors. Moreover, after 2-week treatment, evogliptin dose-dependently reduced whole body fat mass while increasing the proportion of smaller adipocytes. However, insulin sensitivity or plasma lipid levels were not significantly altered. In addition to increased active GLP-1 levels by plasma DPP4 inhibition, evogliptin also enhanced basal metabolic rate without reduction in caloric intake, in contrast to exenatide; this finding suggested evogliptin's effects may be mediated by pathways other than via GLP-1. Evogliptin treatment also differentially increased Ppargc1a expression, a key metabolic regulator, in WAT, but not in skeletal muscle and brown adipose tissue. The increased expression of the downstream mitochondrial gene, Cox4i1, was also suggestive of the potential metabolic alteration in WAT by DPP4 inhibitors. We are the first to demonstrate that pharmacological DPP4 inhibition by evogliptin directly causes fat loss in established obese mice. In contradistinction to exenatide, the fat-loss effect of DPP4 inhibitor is partly attributed to enhanced energy expenditure along with metabolic changes in WAT. These results provide insight into the regulation of energy storage in WAT caused by DPP4 inhibition.